Valorando bens públicos usando dados da economia da felicidade: o caso do seguro-desemprego - Rafael Klanfer Nunes (2013)
This work aims to use the approach of the economics of happiness to value public goods, in particular unemployment insurance. Among the major innovations in relation to what has been done in this area, we highlight the microeconomic approach of our analysis and the treatment of endogeneity that arises from the relationship between income and happiness. The work also presents a literature review, replication of some relevant empirical work as well as a detailed discussion of the methods used. Our estimations suggest that a European individual would be willing to give up of approximately 163 euros of their annual income to get an increase of 1 percentage point in the volume of unemployment insurance benefits that is offered. This value, compared with older works, indicates that Europeans are assigning a higher value to policies of unemployment insurance in the recent years, which in part can be attributed to the crisis that has affected the world in 2008.